2020
DOI: 10.3390/foods9040379
|View full text |Cite
|
Sign up to set email alerts
|

Segmentation of Polish Households Taking into Account Food Waste

Abstract: Currently, food waste is estimated at more than one-third of all food produced, and the primary responsibility for this phenomenon is attributed to households. Therefore, it seems reasonable to take action to limit food waste and to raise awareness about this link in the chain. To develop and implement educational programs addressed at consumers it is necessary to understand the factors determining food waste in households. Segmentation is a tool that can help effectively reach consumers who are to the greates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 48 publications
0
8
0
5
Order By: Relevance
“…On the one hand, this may mean that food is important to people in this cluster, and on the other hand, they buy too much and do not always manage to get the most out of it. Bilska et al (2020b) observed the lowest frequency of throwing away 13 product groups in the cluster that declared a good financial situation. In the same study, cluster C (consisting of households with at least three adults, rather without children), declaring the best financial situation, used wilted vegetables and fruit to prepare other dishes significantly more often.…”
Section: Discussionmentioning
confidence: 97%
“…On the one hand, this may mean that food is important to people in this cluster, and on the other hand, they buy too much and do not always manage to get the most out of it. Bilska et al (2020b) observed the lowest frequency of throwing away 13 product groups in the cluster that declared a good financial situation. In the same study, cluster C (consisting of households with at least three adults, rather without children), declaring the best financial situation, used wilted vegetables and fruit to prepare other dishes significantly more often.…”
Section: Discussionmentioning
confidence: 97%
“…Niezależnie od płci oraz wieku raczej niechętnie nabywają tego typu produkty i tylko niespełna 10% respondentów deklarowało, że kupuje niekształtne owoce i warzywa oraz produkty z krótką datą ważności. Kupowanie zbyt dużej ilości towarów, kupowanie na zapas, zakupy impulsywne, niezwracanie uwagi na datę przydatności do spożycia są czynnikami powodującymi, że konsumenci marnują ogromne ilości żywności (Bilska et al 2020). W aspekcie postępowania respondentów z żywnością w domu istotnym czynnikiem jest sposób jej przechowywania.…”
Section: Marnotrawstwo żYwności W Gospodarstwach Domowych I Praktyki Konsumpcyjneunclassified
“…Segmentacja konsumentów przeprowadzona przez Bilską i wsp. [3] wskazuje, że jednoosobowe i dwuosobowe gospodarstwa domowe bez dzieci cechują się wysoką częstotliwością wyrzucania żywności z powodu zbyt dużego opakowania. Ponad 65 % badanych wskazała, że stara się zagospodarować nadwyżki żywności.…”
Section: Wyniki I Dyskusjaunclassified
“…Przyczyny wyrzucania żywności i produkty najczęściej wyrzucane przez studentów biorących udział w badaniu są analogiczne do wskazanych przez Bilską i wsp. [3], którzy przeprowadzili w 2019 r. badanie ankietowe na grupie 1115 dorosłych Polaków.…”
Section: Wyniki I Dyskusjaunclassified